1993
DOI: 10.2307/3283620
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Activity of Tetracycline against Brugia pahangi Infection in Jirds (Meriones unguiculatus)

Abstract: The ability of oral tetracycline to inhibit the development of third-stage infective larvae (L3) of Brugia pahangi to adult worms in jirds was studied using 2 experimental protocols. Jirds treated with 1.4% tetracycline in drinking water for a period beginning 30 days before inoculation of L3 until 30 days post-inoculation (DPI) had 97% reduction in adult worm recovery compared to untreated controls. Jirds that received 1.2% tetracycline in drinking water beginning 1 day before until either 12 or 26 DPI had ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 0 publications
1
53
1
Order By: Relevance
“…The results reported here (Table I) on the prophylactic activity of tetracycline against B. pahangi infection in jirds agree with those of Bosshardt et al (1993)-Our present paper, however, show that 0.3% tetracycline in drinking water is enough to prevent B. pahangi infection, while Bosshardt et al used dosages of 1.2% and 1.4%. We should consider that a 0.3% drinking water dosage (which corresponds to an intake of approximately 150 mg/kg/day) is a standard dosage for chemotherapy of rickettsial diseases.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results reported here (Table I) on the prophylactic activity of tetracycline against B. pahangi infection in jirds agree with those of Bosshardt et al (1993)-Our present paper, however, show that 0.3% tetracycline in drinking water is enough to prevent B. pahangi infection, while Bosshardt et al used dosages of 1.2% and 1.4%. We should consider that a 0.3% drinking water dosage (which corresponds to an intake of approximately 150 mg/kg/day) is a standard dosage for chemotherapy of rickettsial diseases.…”
Section: Discussionsupporting
confidence: 70%
“…As discussed elsewere Bandi et al, 1999), the inhibitory effects of tetracycline on the embryogenesis of D. immitis and B. pahangi could derive from phenomena like cytoplasmic incompatibility or medea (Werren & O'Neill, 1997). The developmental inhibition observed by Sucharit et al (1978) and the prophylactic effects reported here and in Bosshardt et al (1993) imply effects on well-developed larvae (first stage larva-L3 and L3-adults). These effects cannot derive from cytoplasmic incompatibility.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…(Henkle-Du« hrsen et al 1998;Bandi et al 1998), suggesting the possibility of a new approach to the chemotherapy of a range of ¢larial infections. In experimental infection of jirds with Brugia, tetracycline was found to be prophylactic (although not curative) (Bosshardt et al 1993). Recent studies on oxytetracycline therapy in vivo with L. sigmodontis in mice demonstrated ¢larial growth arrest and infertility had no e¡ect on Acanthocheilonema viteae, which does not carry Wolbachia endosymbionts, and other antibiotics, ine¡ective against rickettsial bacteria, did not a¡ect Litomosoides development , evidence that the anti-¢larial e¡ects were mediated through action on the Wolbachia bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and apparent stability of the Wolbachia^¢laria symbiosis suggest that Wolbachia plays an as yet unknown role in the biology of ¢larial nematodes. The activity of tetracycline against ¢larial worm development (Bosshardt et al 1993;Genchi et al 1998;J. W. McCall, personal communication) could thus derive from the action of tetracycline on Wolbachia endosymbionts, even though the possibility that tetracycline has a direct toxic e¡ect on ¢larial nematodes (or an indirect e¡ect mediated by endosymbionts di¡erent from Wolbachia) cannot be dismissed.…”
Section: Discussionmentioning
confidence: 99%